Inovasi Lapis Pondasi Atas CTB (Cement Treated Base) Menggunakan Subtitusi Pofa dan Limbah Cangkang Kerang Hijau - Pratama, Raka Aditya (Jurnal Proyek Teknik Sipil, 2023)
During the current administration, the construction sector, especially toll road infrastructure in Indonesia, has increased. This will increase the amount of cement production to meet construction needs. Even though the cement industry is one of the contributors to gas emissions. In addition, the plantation sector can be optimized as an alternative construction material. Such as palm shell waste (POFA), which contains the same content as cement. The fisheries sector can also be optimized as an alternative construction material. such as green mussel shells which have the same content as cement, which is pozzolanic. Based on these problems, the purpose of this research is to optimize palm oil shell waste and green mussel shells as cement substitution materials in CTB to reduce gas emissions. The method used is research and experimentation by partially substituting cement by 10% and 20% using POFA. 5% and 10% use green mussel shell waste which will later be compared with the CTB Job mix formula which complies with the general specifications by testing the compressive strength of concrete and analysis of CTB work unit prices per 1 m3. The results of this study revealed that the highest compressive strength of 5.5 MPa occurred in 20% POFA substituted CTB and 10% green mussel shells. This compressive strength is higher than Normal CTB. However, from the results of price analysis it can be seen that 20% POFA substitution CTB and 10% green mussel shells require a 3.7% higher cost than the Normal CTB price or a difference of Rp.19,792.22.